STRUKTUR KEPEMILIKAN SEBAGAI MEKANISME KONTROL IDIOSYNCRATIC RISK UNTUK MENINGKATKAN NILAI PERUSAHAAN - Monica Monica; Suwandi Ng (Dinamika Akuntansi Keuangan dan Perbankan, 2018)
This research aims to investigate the impact of ownership structure (foreign ownership, promoter ownership, managerial ownership, and public ownership) on firm value mediated by idiosyncratic risk. The population used is the whole companies listed in Indonesian Stock Exchange (BEI) on the period of 2013-2017. The number of samples is 182 companies each year, which was selected by purposive sampling method. This research uses documentary data, i.e. the annual report and financial statements. Path analysis used to analyze data and hypothesis mediation analysed by using Sobel test. The results show that foreign ownership, managerial ownership, and public ownership have a negative and significant impact on the idiosyncratic risk, while the promoter ownership has a positive and significant impact on the idiosyncratic risk. Idiosyncratic risk and promoter have a negative and significant impact on firm value, foreign ownership has a positive but insignificant impact on firm value, while managerial ownership and public ownership have a positive and significant impact on firm value. In addition, idiosyncraticn risk can madiate the impact of ownership structure (foreign ownership, promoter ownership, managerial ownership, and public ownership) on firm value. The implication of this research is that companies and investors can consider the importance of idiosyncratic risk through diversification of ownership structure as a mechanism for achieving firm value. The idiosyncratic risk is expected to assist the investor in making business decisions as they reflect the company’s specific information and fluctuate accordingly and the movement is independent of market movements. Keywords : ownership structure, foreign ownership, promoter ownership, managerial ownership, public ownership, idiosyncratic risk, and firm value